Duits Expressionisme. (Nieuwpoort : Florizoone - XXth Century Fine art.)
Beckman, Max ; Dix, Otto ; Ensor, James ; Heckel, Erich ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kokoschka, Oskar ; Kollwitz, Kathe ; Marc, Franz ; Masereel, Frans ; Nolde, Emil ; Schmidt-Rottluff, Karl ; Wiegers, Jan
biografie
Duits Expressionisme, Florizoone - XXth Century Fine art, Nieuwpoort, s.a.
boek
Keywords: Duitsland